2020
DOI: 10.31235/osf.io/zyp3f
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Politische Soziologie der Corona-Proteste

Abstract: In the research project "Political Sociology of the Corona Protests", researchers from the Department of Sociology at the University of Basel are empirically investigating the current Corona protests in Switzerland and Germany. The aim of the research is to analyse the motivation, values and beliefs of the participants in rallies, actions and demonstrations directed against the corona-related measures.In order to be able to comprehensively investigate these new protests, a broad empirical approach (mixed-metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
65
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(84 citation statements)
references
References 0 publications
6
65
0
11
Order By: Relevance
“…While we focused on the Amish and Mennonites, the theoretical mechanisms proposed could apply to other religious traditions as well. For example, research on German protesters of government COVID-19 restrictions identified that only a tiny percentage were Christian (Nachtwey et al 2020). More research is needed comparing perceptions of government restrictions and the pandemic among people within the same religious traditions who have the same moral cores but reside in different countries or contexts.…”
Section: Discussionmentioning
confidence: 99%
“…While we focused on the Amish and Mennonites, the theoretical mechanisms proposed could apply to other religious traditions as well. For example, research on German protesters of government COVID-19 restrictions identified that only a tiny percentage were Christian (Nachtwey et al 2020). More research is needed comparing perceptions of government restrictions and the pandemic among people within the same religious traditions who have the same moral cores but reside in different countries or contexts.…”
Section: Discussionmentioning
confidence: 99%
“…German public opinion toward the government's policies has fluctuated. Protests against mask and lockdown policies have recurred, with political authorities and media accused of overreaction ( Nachtwey, Frei, and Schäfer 2020 ). Support has also been affected by the problems of the vaccination program.…”
Section: Why Emergency? Reflections On the Practice And Rhetoric Of Exceptionalismmentioning
confidence: 99%
“…1 Trotz der zunehmenden Thematisierung der Auswirkungen auf Frauen im Bezug auf die Corona-Krise fehlt eine geschlechtsspezifische Analyse in der Untersuchung der aktuell in Deutschland, in der Schweiz und in Österreich stattfindenden Corona-Proteste. Wenngleich bislang keine empirische Einzel-Untersuchung zu den Frauen, die an den Corona-Protesten in den deutschsprachigen Ländern teilnehmen, vorhanden ist, so lässt sich zumindest aus den Studien von Nachtwey et al (2020) und Koos (2021) Folgendes gewinnen: Bei den protestierenden Frauen handelt es sich vornehmlich um bürgerliche Frauen mit höherem Bildungsabschluss und deutscher respektive österreichischer oder schweizerischer Staatsbürgerschaft, die gegenüber -1 Die aufgelisteten Momente sind nicht die einzigen Gefährdungen für Frauen unter Coronabedingungen. Zu ihnen gehören auch die steigende Gewalt gegen Frauen unter Ausgangsbeschränkungen (Steinert/Ebert 2020) oder die massiven esoterischem Denken offen sind, die Impfthematik als relevant ausweisen und ihre Sorge um Kinder ausdrücken.…”
Section: Introductionunclassified